High Frequency Oscillatory Ventilation - AC Bryan; D Bohn (Canadian Respiratory Journal)
High frequency oscillatory (HFO) ventilation using low tidal volume and peak airway pressures is extremely efficient at eliminating carbon dioxide and raising pH in the newborn infant with acute respiratory failure. Improvement in oxygenation requires a strategy of sustained or repetitive inflations to 25 to 30 cm H2O in order to place the lung on the deflation limb of the pressure-volume curve. This strategy has also been shown to decrease the amount of secondary lung injury in animal models. Experience of the use of HFO ventilation as a rescue therapy as well as several published controlled trials have shown improved outcomes and a decrease in the use of extracorporeal membrane oxygenation when it has been used in newborns.